FULFILLMENT OF THE RIGHT TO SPECIAL PROTECTION FOR CHILDREN IN CONFLICT WITH THE LAW (ABH) IN THE CITY OF TERNATE - Arisa Murni Rada; Muhaimin Limatahu; Ahmad Mufti (Cepalo, 2023)
This research focuses on testing the cluster of children's rights with indicators of the fulfillment of special protection for children, specifically children in conflict with the law (ABH) as perpetrators; this is based on the fact that a child is at very high risk of being violated by his human rights when he has to be involved in the criminal justice system. The method used is empirical juridical or sociological legal research that examines the legal provisions that apply and what happens in society. The sociological juridical and statutory approach examines all regulations related to the legal issues under study. The data obtained were analyzed descriptively and qualitatively and used the deductive and inductive methods in concluding. The study results show that the fulfillment of special protection rights for children by law enforcement and the Regional Government of Ternate City is not optimal, even though several cases have been handled through a restorative justice approach in handling ABH. The support from the Regional Government of the City of Ternate realizes the fulfillment of ABH rights. It accelerates the status of a Child-Friendly City by providing the necessary facilities such as ABH special needs, special detention cells, recreation activities, social advocacy, accessibility, education, health, religion, and other needs through establishing a Unit. The Technical Implementer of the Area for the Protection of Women and Children (UPTD PPA) is constrained internally and externally, namely the unavailability of the Regional Regulation on Child Protection as a legal basis at the regional level, the unavailability of rehabilitation facilities for drug addict children and the low level of public understanding of the settlement of restorative justice which prioritizes children's interests.